Synthesis and Characterization of Hydroxyapatite Derived from Pleco Fish (Hypostomus Plecostomus) Bone Waste via Calcination and Ball Milling for Biomedical Applications - Sari, Nurfitri Rahmi; Thoriq, Andika; Gunawarman; Nanda, Is Prima; Indra, Ade; Yetri, Yuli; Verdian, Riza (Department of Mechanical Engineering, Universitas Andalas, 2025)
Hydroxyapatite (HA), a calcium phosphate-based bioceramic, is widely recognized for its excellent biocompatibility and bioactivity, making it suitable for biomedical applications. This study aims to synthesize HA from waste bones of the pleco fish (Hypostomus plecostomus), a natural source of calcium and phosphate that is underutilized in West Sumatera. The synthesis was conducted through calcination at 900 °C followed by mechanical refinement using ball milling for 3, 6, and 9 hours. X-ray diffraction (XRD) analysis confirmed the formation of crystalline HA with dominant peaks at 25.9°; 31.8°; and 32.9°, which remained stable across all milling durations.